Receiving The COVID-19 Vaccine and Its Correlation with Post COVID-19 Long Term Morbidity - Dawah, Ahmed Mahdi; Ghardallou, Meriam; Buthaina A Rashid (National Journal of Community Medicine, 2024)
Back ground: Long-coronavirus disease is the long-term consequences of COVID-19 infection experienced by individuals who are infected with the virus. Signs, symptoms, and problems that persist or worsen following an acute COVID-19 infection are collectively referred to as long COVID. This study tries to determine the correlation between vaccination status and the post-COVID long-term effects in vaccinated versus non-vaccinated infected individuals. Methodology: It was a cross-sectional descriptive design, encompassing 416 individuals. Study cases represented vaccinated individuals who were infected and were suffering from the long-term consequences of COVID-19, as opposed to non-vaccinated infected individuals. Individuals who were neither infected, vaccinated, or unvaccinated considered as a reference group for estimating the correlation utilizing Odds ratio (OR). Result: This study revealed that vaccinated individuals were more commonly affected by weakness (OR= 0.93; 95% CI 0.49-1.7), joint pain (OR= 0.7; 95% CI 0.41-1.4), and concentration problems (OR= 0.87; 95% CI 0.44-1.7) so that present study didn’t notify significant statistical findings for post-COVID conditions risks regarding to vaccination status. Conclusion: The correlation between vaccinated and non-vaccinated individuals who develop post-COVID-19 conditions showed that risk factors for developing these conditions were independently associated with vaccination status among infected participants.